Adsorption and Detection of DNA Dendrimers at Carbon Electrodes - Wang, Joseph; Rivas, Gustavo; Fernandes, João Roberto; Jiang, Mian; Lopez Paz, José Luis [UNESP]; Waymire, Russel; Nielsen, Thor W.; Getts, Robert C. (My University, 1998)
Dendritic nucleic acids are highly branched and ordered molecular structures, possessing numerous single-stranded oligonucleotide arms, which hold great promise for enhancing the sensitivity of DNA biosensors. This article evaluates the interfacial behavior and redox activity of nucleic acid dendrimers at carbon paste electrodes, in comparison to DNA. Factors influencing the adsorption behavior, including the adsorption potential and time, solution conditions, or dendrimer concentration, are explored. The strong adsorption at the anodically pretreated carbon surface is exploited for an effective preconcentration step prior to the chronopotentiometric measurement of the surface species. Coupled with the numerous guanine oxidation sites, such stripping protocol offers remarkably low detection limits (e.g., 3 pM or 2.4 femtomole of the 4-layer dendrimer following a 15 min accumulation). The new observations bear important implications upon future biosensing applications of nucleic dendrimers.
Keywords: Adsorptive potentiometry; Biosensors; Carbon paste; Dendrimers; DNA; Nucleic acids